Web-Based Tire Check Application Development - Ardiansyah, Vicky; Hilmy, Muhammad Hilmy; Budiawan, Rezky; Rahayu, Sarwati (Journal Collabits, 2025)
This study investigates the development of a web-based application called Tire Check that can monitor vehicle tire pressure in real-time. This application aims to improve driving safety by providing up-to-date information on tire pressure conditions, which are a major factor causing traffic accidents in Indonesia. This application uses the MPX5700 sensor to measure tire pressure and connects it to a tire pressure monitoring system (TPMS). Analysis, design, implementation, and testing are part of the Waterfall methodology in software development. This application is built with the Laravel framework, using HTML, CSS, and PHP. Its main features include low tire pressure warnings, optimal tire pressure recommendations, and a simple and easy-to-understand user interface. The test results show that the application operates well and can detect tire pressure with 90% accuracy. To ensure that all features work as expected, testing is carried out using the black-box method with positive and negative scenarios. This application reduces the risk of accidents due to flat or burst tires by monitoring tire conditions without manual measuring tools. In addition, additional features such as tire temperature monitoring and compatibility with iOS devices have been developed.